2012
DOI: 10.7226/jtfm.18.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acid Characteristics and Tolerance of Sengon (Paraserianthes falcataria L Nielsen) to Lead

Abstract: This study aimed to find out the lead tolerance of sengon (Paraserianthes falcataria) seedling based on growth performance, tolerance index, and secretion and accumulation of organic acids content. Seedlings were exposed to lead (Pb) with the concentration of 0, 0.5, 1, 1.5, 5, and 10 mM in liquid nutrient culture for 4 days in order to investigate secretion and accumulation of oxalic, malic, and citric content, and for 15 days to examine growth performance and tolerance index. The result showed that tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
2
8
0
3
Order By: Relevance
“…Organic acids such as oxalic acid and malic acid can chelate with Cd to prevent its entrance into roots, and the cadmium phosphate complex that formed by the combination of organic phosphate acid and ions was unavailable to plants (Nazar et al 2012). In the present study, the relative composition of organic acids in the culture solution is the same as in the roots, with oxalic acid dominant, and it is likely that both types of acids have the same function (Setyaningsih et al 2012). This was consisted with the research conducted by Xie et al (2009), who reported that oxalic acid exceeded 98 % of total acids in perennial ryegrass.…”
Section: Discussionsupporting
confidence: 64%
“…Organic acids such as oxalic acid and malic acid can chelate with Cd to prevent its entrance into roots, and the cadmium phosphate complex that formed by the combination of organic phosphate acid and ions was unavailable to plants (Nazar et al 2012). In the present study, the relative composition of organic acids in the culture solution is the same as in the roots, with oxalic acid dominant, and it is likely that both types of acids have the same function (Setyaningsih et al 2012). This was consisted with the research conducted by Xie et al (2009), who reported that oxalic acid exceeded 98 % of total acids in perennial ryegrass.…”
Section: Discussionsupporting
confidence: 64%
“…Media treatment was 1/3 dosage of nutrient culture treated by Pb (NO3) with 6 2 different Pb concentrations i.e. 0, 0.5, 1, 1.5, 5 and 10 mM respectively (Setyaningsih 2012 FeEDTA. During the adaptation and treatment, the aeration was supplied using electrical aerator.…”
Section: Methodsmentioning
confidence: 99%
“…for seedling Special preparation roots, before being dried, considted of soaking them in 1.0 mM H-EDTA for 30 minutes to remove Pb attached on the root surface and rinsed three times in H O (Javris & Leung 2002). (Setyaningsih et al 2012). Chlorosis and necrosis occur red presumably because photosynthetic pigment was damage as a result of decreased production of chlorophyll a and b when Pb exposure increased up to 1500 ppm .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perlakuan yang diberikan adalah penambahan Pb(NO3)2 sebagai sumber Pb yangterdiri lima taraf, yaitu P0 = 0 mg Pb/kg tailing, P1 = 150 mg Pb/kg tailing, P2 = 300 mg Pb/kg tailing, P3 = 450 mg Pb/kg tailing (Setyaningsih et al, 2012) …”
Section: Rancangan Percobaanunclassified